Peranan Guru dalam Meningkatkan Disiplin Belajar Siswa Studi Kasus pada Siswa yang Bermasalah - Yuhasnil Yuhasnil; Yandi Agusmardi (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study was to describe the role of teachers in improving student discipline in students with problems at SMK N 3 Payakumbuh. This type of research is descriptive qualitative research. The results of this study are: (1). The teacher's role in improving the learning discipline of students with problems is to provide guidance in improving discipline in entering class on time, informing and explaining the rules that exist at school, providing examples of disciplinary attitudes and behavior in class, giving warnings to students if there are those who violate school rules, give sanctions if there are frequent violations, hold mutual cooperation twice a month and facilitate cleaning tools in improving hygiene discipline, provide learning support facilities in the library; (2). Factors that affect the discipline of students who have problems are the lack of family attention, economic factors and frequent commotion at home, the location of the school is close to the highway while the traffic passing by makes it noisy and classmates who are often nosy while studying, there are less controlled relationships in the classroom. the middle of society. The conclusion of the study is that teachers play an important role in improving student discipline with problems, one of which is by providing guidance, explaining rules, providing examples, giving warnings and sanctions for violators of rules at school. Keywords: Student Learning Discipline, Teacher Role